INTEGRATED FOOD SECURITY MANAGEMENT USING SIPEKAN (FOOD SECURITY MONITORING INFORMATION SYSTEM) - Sasana, Hadi; Purbaningrum, Catarina Wahyu Dyah; Rohmah, Siti; Afriyanti, Afriyanti; Rochmadi, Imsak; Suprapto, Agus; Bharata, Risma Wira; Negara, Julius Galih Prima (Universitas Tidar, 2025)
The study aims to investigate an integrated food security management using the Food Security Monitoring Information System, called “SIPEKAN” (Sistem Informasi Pemantauan Ketahanan Pangan) in Gunungkidul Regency, Yogjakarta, Indonesia. This study is a research and development-type of research (Research and Development) with the development model presented by Plomp (2013). The target groups are the community, farmers, agricultural extension workers, the agricultural service, the trade service, and the local government of Gunungkidul Regency. This research is expected to provide an integrated food security management equipped by the Food Security Monitoring Information System, called